A retrospective study of systemic manifestations in systemic lupus erythematosus in a tertiary care centre - Budhrani, Deepmala; Raja, Pooja; Jadwani, Monal; Chauhan, Khushbu; Patel, Bharti; Bhuptani, Neela V. (International Journal of Research in Dermatology, 2019)
Background: Systemic lupus erythematosus (SLE) is an autoimmune disease involving multiple organ systems. Other than cutaneous manifestations, thorough examination and investigations for systemic involvement should also be done. The objective is to study the prevalence of various systemic manifestations in SLE patients in a tertiary care hospital. Methods: A retrospective study was conducted from April 2009 to August 2018 on the patients who fulfilled the Systemic Lupus International Collaborating Clinics (SLICC) criteria for SLE. A total of 63 cases of SLE were extracted from the case record for the study. Each case was subjected to detailed history, examination, investigations including complete blood count, liver function test, renal function test, blood sugar, urine routine examination, ECG, X-ray of chest and involved joints, USG abdomen, pulmonary function test. Ours being a resource limited set-up, ANA, ENA profile and echocardiography were done whenever patient could afford. Results: In present study of 63 cases of SLE 94% were females. Mean age was 30 years. Various systemic involvement was present, amongst them musculoskeletal system was the most common system involved with 60 (95%) patients, followed by hematological system 48 (76%), renal system 37 (59%), neuropsychiatric system 29 (46%), gastrointestinal system 28 (44%), reproductive system 27 (43%), cardiovascular system 25 (40%). Other systems with ophthalmic involvement 23 (21%), hepatobiliary system 22 (35%), respiratory system 17 (27%), endocrine involvement 13 (28%) and malignanacy was present in 2 (3%) cases. Conclusions: SLE is protean in its manifestations. Thorough knowledge about the systemic involvement will help in tailoring the treatment in case of SLE.